A Cytogenetic Study on the Efficacy of Chyawanprash Awaleha as an Antioxidant in Oral Premalignant Cancer. (1st December 2014) - Uma, A. N.; Kotasthane, Dhananjay S.
Abstract : Background . Chyawanprash awaleha (Cp) is an Ayurvedic rasayana formulation and is used as a genoprotective agent. Objective . The present cytogenetic study has been done to investigate the efficacy of Cp against betel quid chewers suffering from oral precancerous lesions through satellite association (SA) assay. Materials and Methods . The frequency of SA was analyzed in 21 betel quid chewing oral precancerous lesions patients and then they were divided into 2 groups. Group 1 consisted of 15 patients, advised to quit betel quid chewing and fed with 20 gms of Cp, twice a day for three months. Group 2 consisted of 6 patients, who refused Cp feed but accepted to quit betel quid chewing. At the end of three months, both groups were assessed cytogenetically. Results . The frequency of SA was statistically significant in both groups, but an elevated mean difference was observed more in Group 1 than in Group 2. Conclusion . The study indicates that betel quid cessation reduces the effect of DNA damage in oral precancerous lesions. But the increased mean difference in SA in Group 1 compared to Group 2 clearly indicates that Cp can further minimize the genotoxic effect caused by mutagenic agents present in betel quid.